Correlation Between Alvarado Score with Surgical Findings in Acute Appendicitis Patients at RSUD Dr. H. Chasan Boesoirie Ternate - A. Mustafa, Fitria Anggaina; Hidayat, Ferdian; M. Selomo, Prita Aulia (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2024)
Acute appendicitis is the most common cause of emergency surgery in the world. Patients who need immediate surgery compared to patients under active observation often difficult to identified, so several system scores have been found including Alvarado score which based on clinical findings. Delayed of surgical treatment results in the progression of this disease. Perforation were mostly found at higher Alvarado scores. This study aims to determine the correlation between the Alvarado score with surgical findings of acute appendicitis patients at RSUD Dr. H. Chasan Boesoirie Ternate. This research is an observational analytical study with a cross-sectional design using secondary data in the form of medical record data of acute appendicitis patients who underwent surgery at RSUD Dr. H. Chasan Boesoirie Ternate during 2020-2022 period who met the inclusion and exclusion criteria amounted to 49 samples. Data taken included age, gender, Alvarado score and surgical findings. The samples were then analyzed univariately and bivariately using Spearman's correlation. Characteristics of acute appendicitis patients were the majority in the age group 17-25 years (46.9%), male (63.3%), Alvarado score group 7-10 (55.1%) and surgical findings of perforation (65, 3%). Based on bivariate analysis, p = 0.019 (p<0.05) was obtained, which means there was a significant relationship between the Alvarado score and the surgical findings of acute appendicitis patients at RSUD Dr. H. Chasan Boesoirie Ternate.